2016
DOI: 10.1002/2016gl070304
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing residual trapping of supercritical CO2 via cyclic injections

Abstract: We utilize synchrotron X‐ray tomographic imaging to investigate the pore‐scale characteristics and residual trapping of supercritical CO2 (scCO2) over the course of multiple drainage‐imbibition (D‐I) cycles in Bentheimer sandstone cores. Capillary pressure measurements are paired with X‐ray image‐derived saturation and connectivity metrics which describe the extent of drainage and subsequent residual (end of imbibition) scCO2 trapping. For the first D‐I cycle, residual scCO2 trapping is suppressed due to high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 48 publications
6
66
0
Order By: Relevance
“…Furthermore, and importantly, these characteristics’ curves, and the associated residual gas and water saturations were modified based on Herring et al .’s data for the WAG scCO 2 ‐brine floods (Figs. and ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, and importantly, these characteristics’ curves, and the associated residual gas and water saturations were modified based on Herring et al .’s data for the WAG scCO 2 ‐brine floods (Figs. and ).…”
Section: Methodsmentioning
confidence: 99%
“…For the first WAG cycle we used the values of the Sco 2 r (residual CO 2 saturation) and Sco 2 i (initial CO 2 saturation) of the intermediate‐wet rock. Then for cycles 2–5 the Sco 2 r was enhanced based on the experimental studies . For all the five WAG cycles the relationship of the Sco 2 r versus Sco 2 i followed Pentland's et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the optimization of the WAG technique to improve oil production while keeping the injection costs reasonable . In the context of CO 2 geological storage, the WAG technique has been studied using experimental methods and numerical modeling …”
Section: Introductionmentioning
confidence: 99%
“…While based on core scale experiment, Saeedi et al . reported that residual gas saturation is independent of the number of cycles, Herring et al . found by pore‐scale experiments that an increase in the number of injection cycles can enhance residual trapping.…”
Section: Introductionmentioning
confidence: 99%